Corrosion of Zn-Ni coated reinforcing steel in simulated concrete pore solutions - Bučko, Mihael M.; Radović, Ljubica M.; Dimitrijević, Marko N.; Karkalić, Radovan M.; Bajat, Jelena B. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: The anticorrosion protection of steel reinforcement bars in concrete is a critical concern in civil engineering, particularly for the construction of concrete structures intended for military applications. Currently, the most important methods for achieving this protection include the application of coatings on steel rebar (such as epoxy or hot-dip galvanized zinc), the use of stainless-steel rebar, composite rebars, or high-performance concrete that incorporates corrosion inhibitors, surface sealers, silica fume, or fly ash admixtures.Methods: This study aims to determine whether an electroplated Zn-Ni coating of sufficient thickness can offer better long-term corrosion resistance to reinforcing steel in concrete compared to the traditional pure Zn coating typically used for this purpose. The Zn-Ni coatings produced were 40 µm thick and contained approximately 13 mass.% Ni. Scanning electron microscopy revealed a smooth and homogeneous surface morphology, although microcracks extending through the entire coating depth were observed. The protective effectiveness of the coatings was evaluated using electrochemical impedance spectroscopy, with samples immersed in various electrolytes that simulate the chemical environments present in different types of concrete.Results: The measurements indicated a significantly slower dissolution rate of the corrosion product formed on the Zn-Ni coating in chloride-rich environments, compared to pure Zn.Conclusion: It can be concluded that Zn-Ni alloy presents a viable alternative to pure Zn for protecting steel in concrete structures where high chloride penetration is anticipated.
Keywords: steel rebar corrosion; Zn-Ni coating; concrete pore solution; electroplating